The relationship between Myth and Philosophy dialectic of relevance and opposition - إلياس, سوسان; المحمود, سارة (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research will discuss two different fields of knowledge with which human thought deals, namely the mythological field and the philosophical field, and the relationship between them are related and contradictory. The research focused on studying and analyzing the linguistic and idiomatic significance of each of the concept of Myth and philosophy in the first place and then revealing different visions about the existing relationship, in the first direction, it looked at the legend in terms of its relationship to philosophy to establish some of the positive connections, while the second opposing trend went to the complete separation between myth and philosophy based on the opposition that this trend established between Metus and Logos. By standing at the two directions in determining the nature of the relationship between myth and philosophy, we find that the first direction works on melting the two modes of thinking into one crucible and in one epistemological channel, and the second direction claims to disconnect between the two types of thinking, so there is nothing that links them except the hostility.